Optimizing patient transportation in large hospitals - Oliveira, Ruan Myller Magalhães de; Queiroz, Layane Rodrigues de Souza; Queiroz, Thiago Alves de (Brazilian Journal of Production Engineering, 2024)
This work handles the problem of picking up and delivering patients among the distinct units of a hospital. This problem arises in hospitals that occupy a large geographic area and, hence, they have several units with different services from each other. The problem assumes a fleet of vehicles, each with a limited transport capacity. Requests for patients' transportation are received over the day and are completely unknown once released. The problem's objective is to determine routes, updated dynamically, for each vehicle so that the total weighted tardiness associated with servicing the requests is minimal. The proposal of this work relies on a re-optimization heuristic based on policies that use characteristics from the patients and the hospital, besides a tabu search metaheuristic. The heuristic approach can provide satisfactory solutions to the problem, considering instances of different sizes.
Keywords: Patient Transportation; Pickup and delivery problem; Reoptimization heuristic; Tabu search